The effects of training impulse control on simulated driving. (October 2018) - Hatfield, Julie; Williamson, Ann; Kehoe, E. James; Lemon, James; Arguel, Amaël; Prabhakharan, Prasannah; Job, R. F. Soames
Highlights: Performance on response inhibition tasks improved with training. Training refined in a series of two studies in order to promote transfer. Very little evidence of less risky simulated driving after training. Weak and inconsistent relationships between behavioural and self-report measures of impulse control. Abstract: There is growing interest in young driver training that addresses age-related factors, including incompletely developed impulse control. Two studies investigated whether training of response inhibition can reduce risky simulated driving in young drivers (aged 16–24 years). Each study manipulated aspects of response inhibition training then assessed transfer of training using simulated driving measures including speeding, risky passing, and compliance with traffic controls. Study 1 (n = 65) used a Go/No-go task, Stop Signal Task and a Collision Detection Task. Designed to promote engagement, learning, and transfer, training tasks were driving-relevant and adaptive (i.e. difficulty increased as performance improved), included performance feedback, and were distributed over five days. Control participants completed matching "filler" tasks. Performance on trained tasks improved with training, but there was no significant improvement in simulated driving. Study 2 enhanced response inhibition training using Go/No-go and SST tasks, with clearer performance feedback, and 10 days of training. Control participants completed testing only, in order to avoid any possibility of training response inhibition in the filler tasks. Again performance on trained tasks improved, but there was no evidence of transfer of training to simulated driving. These findings suggest that although training of sufficient interest and duration can improve response inhibition task performance, a training schedule that is likely to be acceptable to the public does not result in improvements in simulated driving. Further research is needed to investigate whether response inhibition training can improve risky driving in the context of real-world motivations for risky driving.